2011
DOI: 10.1029/2010jd015152
|View full text |Cite
|
Sign up to set email alerts
|

Emissions of black carbon, organic, and inorganic aerosols from biomass burning in North America and Asia in 2008

Abstract: [1] Reliable assessment of the impact of aerosols emitted from boreal forest fires on the Arctic climate necessitates improved understanding of emissions and the microphysical properties of carbonaceous (black carbon (BC) and organic aerosols (OA)) and inorganic aerosols. The size distributions of BC were measured by an SP2 based on the laser-induced incandescence technique on board the DC-8 aircraft during the NASA ARCTAS campaign. Aircraft sampling was made in fresh plumes strongly impacted by wildfires in N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

42
305
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(361 citation statements)
references
References 120 publications
(159 reference statements)
42
305
4
Order By: Relevance
“…This unimodal result is consistent with aged biomass-burning observations found globally in the previous field studies (Capes et al, 2008;Janhäll et al, 2010;Kondo et al, 2011).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This unimodal result is consistent with aged biomass-burning observations found globally in the previous field studies (Capes et al, 2008;Janhäll et al, 2010;Kondo et al, 2011).…”
Section: Discussionsupporting
confidence: 81%
“…Capes et al (2008) show a similar aged BB size-distribution median diameter over western Africa during the DABEX campaign (D pm = 240 nm). The ARCTAS-B campaign over northern Canada sampled similar boreal pyrogenic outflow and collected very similar aged distributions of BC and OC constituents (D pm = 224 ±14 nm, σ = 1.33 ±0.05) (Kondo et al, 2011).…”
Section: Observed Size Distributionsmentioning
confidence: 99%
“…The coagulation of particles in ambient air is dominated by Brownian motion, a slow process for particles in the accumulation mode (Seinfeld and Pandis, 1998). Therefore, the similarity in VED size distribution for the rBC core between clean days and the pollution episode indicates that the measured rBC particles are likely from biomass burning emissions, given that fossil fuel and biomass burning tend to have different rBC size distributions and that the peak diameter measured in this study is similar to the reported rBC peak diameter from biomass burning plumes (range ∼ 187-193 nm; see Kondo et al, 2011;Sahu et al, 2012;Taylor et al, 2014).…”
Section: Mass Size and Mixing State Of Rbc Aerosolsupporting
confidence: 71%
“…The ARCTAS field campaign took place as a part of the international POLARCAT framework (POLar study using Aircraft, Remote sensing, surface measurements and models, of Climate, chemistry, Aerosols, and Transport; see Law et al, 2014 , and www.polarcat (Jacob et al, 2010;Law et al, 2014). The spring phase (ARCTAS-A) which happened during April 2008, was concurrent with an unusually higher number of Siberian fires, which subsequently caused higher concentrations of carbonaceous aerosols (Fuelberg et al, 2010; Kondo et al, 2011;Liu et al, 2015;Matsui et al, 2011;McNaughton et al, 2011;Spackman et al, 2010;Wang et al, 2011;Warneke et al, 2009). Figure Oceanic and Atmospheric Administration (NOAA) Global Monitoring Division (GMD), where a particle soot absorption photometer (PSAP) is used for measuring BC light absorbing coefficient at three wavelengths (476, 530, and 660 nm) (Bodhaine, 1989;Bond et al, 1999;Delene and Ogren, 2002 ; Data is available at 10 https://esrl.noaa.gov/gmd/aero/net/).…”
mentioning
confidence: 99%